2020
DOI: 10.1002/ijgo.13353
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine infusion of platelet‐rich plasma is a treatment method for patients with intrauterine adhesions after hysteroscopy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Administration of PRP has achieved encouraging results in the treatment of thin endometrium, intrauterine adhesions, endometrium-associated infertility, and recurrent implantation failure (RIF). [33][34][35][36] Our previous research found that PRP possessed antiinflammatory effects on LPS-induced endometritis in mice. 19 Whereas, the repair mechanisms in endometrial tissues remains largely unexplored.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Administration of PRP has achieved encouraging results in the treatment of thin endometrium, intrauterine adhesions, endometrium-associated infertility, and recurrent implantation failure (RIF). [33][34][35][36] Our previous research found that PRP possessed antiinflammatory effects on LPS-induced endometritis in mice. 19 Whereas, the repair mechanisms in endometrial tissues remains largely unexplored.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, biotherapy has been gaining popular attention and scientific endorsement for the treatment of endometritis. Administration of PRP has achieved encouraging results in the treatment of thin endometrium, intrauterine adhesions, endometrium‐associated infertility, and recurrent implantation failure (RIF) 33–36 . Our previous research found that PRP possessed anti‐inflammatory effects on LPS‐induced endometritis in mice 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al [ 27 ]. conducted a retrospective cohort study to explore the effectiveness of PRP by comparing the IUA scores and postoperative chemical pregnancy rates of the PRP and balloon groups after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the recurrence rate of IUA and improve reproductive prognosis, it is often recommended to assist other prevention and treatment measures for comprehensive management of adhesions after the surgery (16-18). These measures mainly include devices to keep opposing endometrial surfaces separated, such as intrauterine device (IUD) (19), Foley catheter balloon (20), auto-crosslinked hyaluronic acid (ACP) gel (21)(22)(23)(24), and interventions to promote endometrial regeneration, such as estrogen (25,26), stem cell (27)(28)(29), stem cell exosome (30), amniotic epithelial cells (31), granulocyte colony stimulating factor (32), platelet rich plasma (33), aspirin (34), etc. However, current effectiveness is still not ideally.…”
Section: Introductionmentioning
confidence: 99%